A soluble garlic polysaccharide supplement alleviates fatigue in mice - Tianyi Li; Chanyuan Xie; Zhenyang Tian; Ran Chai; Yuan Ren; Jiaxin Miao; Wentao Xu; Shimin Chang; Changhui Zhao (npj Science of Food)
Abstract Garlic polysaccharide (GP) is an inulin-type fructan with potent antioxidant activity, whereas its health-promoting functions are not well explored. In the current study, we established a fatigue model by forcing mice to swim in a water tank for at least one hour every day. We measured changes in body weight, exhaustive swimming time, and biochemical indices related to fatigue in weight-bearing swimming mice fed low (1.25 g/kg-BW) and high doses (2.5 g/kg-BW) of GP by daily gavage for 7 weeks. The soluble GP was extracted from industrial garlic wastes using a patented method. The results indicate that GP improved symptoms by increasing the duration of exhaustive swimming, restoring blood biochemical markers (BUN and BLA), and increasing liver and muscle glycogen reserves in fatigued mice. GP also increased antioxidant enzyme activity (SOD, GSH-Px, and CAT) and restored ATPase activity by activating the AMPK/PGC-1α pathway. Additionally, GP modified the gut microbiota by increasing potentially beneficial bacteria and decreasing harmful bacteria. The increase in Bacteroidota and the decrease in Firmicutes phyla regulate the metabolism of short-chain fatty acids in the gut. In conclusion, GP may be effective in alleviating exercise-induced fatigue through multiple mechanisms and can be developed into health anti-fatigue supplements.